The Devil to Pay in the Backlands out loud - Milano, Luiza (2017)
This text presents the results of a reading aloud experience of the classic novel of Guimarães Rosa, The Devil to Pay in the Backlands. The group reading of this work gave rise to the reflection that will now be presented in three parts: text, voice and listening. It begins with the emphasis given to the markers of orality evidenced in the text, then it approaches the crossing of the passage of different voices in the reading of the novel and discusses the role of listening as the basis of otherness and of the senses. In the course of the work, the phonic aspect of language will be highlighted from an approach that seeks to interpret the relationship between sound and meaning in the dialogue between the field of linguistics and that of literature.